Wage Differentials and Market Imperfections: Some Cross Section Results in Canadian Manufacturing Industries - Jones, J.; Laudadio, L. (Relations industrielles / Industrial Relations, 1975)
The purpose of this paper is to analyse the extent to which factor and product market imperfections are responsible for wage differentials. The conclusion is that without some form of factor market imperfection, the existence of imperfection in the product market cannot explain wage differentials.